MEMBANGUN LEMBAGA KEBERATAN PAJAK INDEPENDEN DAN ADIL - Wahyudi (JOURNAL OF LAW AND NATION, 2022)
The objection agency should be present to resolve tax disputes based on the spirit and spirit of kinship, by means of deliberation to reach consensus. However, the spirit of kinship and mutual cooperation, the principle of harmony, the way of deliberation and the atmosphere of peace, harmony, and peace are still far from what was expected. The legal culture in tax disputes that is not in accordance with the noble values in Pancasila causes tax disputes both in quantity and quality to increase sharply every year. Of the various alternative solutions to build a more independent and fair objection agency, the author chose the second alternative, namely placing the Objection Institution in a separate echelon 2 unit at the Directorate General of Taxes. This Objection Institution unit can be expanded by adding a vertical unit that handles objection disputes in each DGT regional office, but is structurally responsible to the echelon 2 unit of the Objection Agency, not to the head of the regional office. Thus, it is hoped that the Objection Institution will become more independent and fair in examining and deciding tax disputes, so that public confidence in the management of tax revenues by the Directorate General of Taxes will increase.